CYanoTech: A sustainable and innovative management system for toxic cyanobacteria blooming of surface waters with combined energy production, sustainable agriculture, and food safety - Keliri, Eleni; Fotidis, Ioannis A.; Mazur-Marzec, Hanna; Antoniou, Maria G.; Tsiarta, Nikoletta; Neofytou, Giannis; Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2023)
The blooming of toxic cyanobacteria in surface waters worldwide has become more persistent and prevalent, thus affecting a number of economic sectors including the tourism industry, fishery and food industry, water treatment and monitoring industry, and health sector with annual loses in the range of millions of dollars. With so many diverse sectors of modern living being affected by the same problem, it is crucial to develop and apply innovative and sustainable management systems for toxic cyanobacteria that can be easily adapted into current infrastructures. CYanoTech is a two-year project that proposes a novel, sustainable, and innovative management system for mitigating the effects of toxic cyanobacteria blooming in surface waters while combining energy production and promoting sustainable agriculture, and food safety. The CYanoTech system comprises of removal of the excess aquatic biomass (cyanobacteria cells and algae) from water with a low energy non-mechanical separation technology, the treatment of the aquatic biomass for the production of energy and marketable products (fertilizers), and the application of treated and untreated surface water in hydroponic cultures that produces safe for consumptions crops (cyanotoxins-free crops). The energy produced will compensate the total energy needs of the applied treatment processes, further reducing the system’s overall carbon footprint, making it self-sustainable. Life-Cycle-Analysis will be used to prove the system’s sustainability and market accessibility. To achieve all the project aims, the Water Treatment Laboratory- Aqua of the Cyprus University of Technology has partnered up with research groups from the Ionian University in Greece and the University of Gdansk in Poland.